2020
DOI: 10.3389/fimmu.2019.02995
|View full text |Cite
|
Sign up to set email alerts
|

Illumination of PRRSV Cytotoxic T Lymphocyte Epitopes by the Three-Dimensional Structure and Peptidome of Swine Lymphocyte Antigen Class I (SLA-I)

Abstract: To investigate CTL epitope applications in swine, SLA-1 * 1502-restricted peptide epitopes matching porcine reproductive and respiratory syndrome virus (PRRSV) strains were explored by crystallography, biochemistry, and the specific pathogen-free (SPF) swine experiments. First, nine predicted PRRSV peptides were tested by assembly of the peptide-SLA-1 * 1502 (pSLA-1 * 1502) complexes, and the crystal structure of the SLA-1 * 1502 complex with one peptide (NSP9-TMP9) was determined. The NSP9-TMP9 peptide confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The 156 Arg in HLA-B*35:08 was shown to prefer P5 E/D as the secondary anchor residues outside the primary peptide anchor pockets (B and F pocket) (23). In SLA-I molecules, residue 156 also plays a critical role in fixing peptides (30,50,55). The positively charged 156 Arg made the D pocket of SLA-1*04:01 prefer negatively charged P3 residues.…”
Section: Discussionmentioning
confidence: 99%
“…The 156 Arg in HLA-B*35:08 was shown to prefer P5 E/D as the secondary anchor residues outside the primary peptide anchor pockets (B and F pocket) (23). In SLA-I molecules, residue 156 also plays a critical role in fixing peptides (30,50,55). The positively charged 156 Arg made the D pocket of SLA-1*04:01 prefer negatively charged P3 residues.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of viral epitopes to CTLs by SLA-1 plays a key role in swine immunity [ 110 ]. The crystal structure of peptide-SLA-1*1502 (pSLA-1*1502) complexes with one peptide (nsp9-TMP9) (PDB code: 5YLX) provides the structural conformation basis of peptide presentation, and the overall structure is very similar to those of pSLA-1*0401 (PDB code: 3QQ3) and pSLA-3*hs0202 (PDB code: 5H94) [ 110 , 111 , 112 ]. The structural information displayed by the D pocket, as shown in Figure 2 , plays a crucial part in determining and fixing the bound peptides, and provides a structural basis for designing effective peptide vaccines [ 111 ].…”
Section: Current Antiviral Strategies and Prospectsmentioning
confidence: 99%
“…The crystal structure of peptide-SLA-1*1502 (pSLA-1*1502) complexes with one peptide (nsp9-TMP9) (PDB code: 5YLX) provides the structural conformation basis of peptide presentation, and the overall structure is very similar to those of pSLA-1*0401 (PDB code: 3QQ3) and pSLA-3*hs0202 (PDB code: 5H94) [ 110 , 111 , 112 ]. The structural information displayed by the D pocket, as shown in Figure 2 , plays a crucial part in determining and fixing the bound peptides, and provides a structural basis for designing effective peptide vaccines [ 111 ]. Study indicated that RdRp has the maximum number of conserved peptides by identifying SLA-1*1502-restricted potential epitopes peptides from whole genomes of different PRRSV strains; thus nsp9/10/11 (especially RdRp) may be the best targets for designing PRRSV vaccines to induce a CTL response to genetically heterologous strains [ 111 ].…”
Section: Current Antiviral Strategies and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PRRSV targets host restriction factors such as CH25HC for degradation via ubiquitin proteasomal system [18]. Recent studies have shown that PRRSV utilizes E3 ubiquitin ligase ASB8 to increases the stabilization of nsp1α, which in turn inhibits NF-κB activity by targeting the linear ubiquitin chain assembly complex and also SLA-I for proteasome degradation [19,20]. Currently, how PRRSV interacts with cellular ubiquitin system to promote viral replication has remained poorly understood.…”
Section: Introductionmentioning
confidence: 99%